The Fall of Artemis: The Secret Recipe of St. Paul's Slow Disciple-Making in Ancient Ephesus - Christianto, Victor (Sekolah Tinggi Teologi Satyabhakti, East Java, 2025)
The present article explores St. Paul's approximately three-year ministry in Ephesus as a profound case study in transformative disciple-making, which we suggest a term : “slow disciple-making” method. Focusing on Acts chapter 19, it argues that Paul's remarkable breakthrough in undermining the worship of Artemis, culminating in the uprising led by Demetrius, stemmed from a deliberate